Waqf Optimization for Determining Goods Selling Prices - Mulyono Jamal; Iqbal Maulana Firdaus; Sultan Nanta Setia Dien Labolo (al-Afkar, Journal For Islamic Studies, 2025)
Waqf has a significant role in overcoming the problem of poverty and social issues that exist in society, especially in setting prices, because this can make prices better if the handling is also good. The method used in this research is Library Research by taking secondary data from books, journals and other articles. Explains that the role of waqf in pricing is as follows: Financing Production Facilities, Price Subsidies, Development of Logistics Infrastructure, Poverty Alleviation, Education and Training, Research and Development, Price Supervision, Financing Micro, Small and Medium Enterprises.